Synthesis and Characterization of Hfo2@Fe3o4 Core-Shell Nanotubes: Insights into Potential Magnetic Functionalities - Vargas-Norambuena, J; Escrig-Murua, J; Saavedra-Díaz, E (American Chemical Society, 2025)
This study presents the synthesis and characterization of core-shell nanostructures comprising PVP@HfO2@Fe2O3 nanowires and HfO2@Fe3O4 nanotubes. PVP nanofibers were electrospun with an average diameter of approximately 379 nm, onto which HfO2 and Fe2O3 layers were sequentially deposited via atomic layer deposition, resulting in core-shell nanowires averaging 460 nm in diameter. Thermal reduction transformed Fe2O3 into Fe3O4, forming HfO2@Fe3O4 core-shell nanotubes. Characterization using scanning electron microscopy and high-resolution transmission electron microscopy confirmed the core-shell morphology, while energy-dispersive X-ray spectroscopy verified the elemental composition. Surface roughness analysis revealed fractal dimensions indicating increased roughness with thicker shells. X-ray photoelectron spectroscopy analysis identified Fe(II) and Fe(III) oxidation states and confirmed phase transformations from hematite to magnetite. Magnetic measurements demonstrated enhanced coercivity and saturation magnetization in HfO2@Fe3O4 structures compared to initial samples, showcasing the tunability of magnetic properties through core-shell engineering. This work highlights atomic layer deposition’s capability to fabricate precise core-shell nanostructures, offering tailored control over morphology and magnetic behavior for applications in advanced nanotechnologies. © 2025 American Chemical Society.